2020
DOI: 10.1038/s41598-020-65771-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Piezoresistive/Piezoelectric Sensing Characteristics of Carbon Nanotube/PVA/Nano-ZnO Flexible Composite

Abstract: Flexible sensors with a high sensitivity and wide-frequency response are essential for structural health monitoring (SHM) while they are attached. Here, carbon nanotube (CNT) films doped with various PVA fractions (CNT/PVA) and ZnO nanowires (nano-ZnO) on zinc sheets were first fabricated by functionalized self-assembly and hydrothermal synthesis processes. A CNT/PVA/nano-ZnO flexible composite (CNT/PVA/ZnO) sandwiched with a zinc wafer was then prepared by the spin-coating method. The piezoresistive and/or pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Variation of CNT volume fraction contribution to the change in electrical resistance in composites was also explored in [10]. This study showed that the change in CNT volume fraction directly contributes to the electrical resistance change, and, therefore, an optimum composites constituent ratio was confirmed for different loading studies [10]. Magnetostrictive materials have also been of interest in composite research.…”
Section: Introductionmentioning
confidence: 96%
“…Variation of CNT volume fraction contribution to the change in electrical resistance in composites was also explored in [10]. This study showed that the change in CNT volume fraction directly contributes to the electrical resistance change, and, therefore, an optimum composites constituent ratio was confirmed for different loading studies [10]. Magnetostrictive materials have also been of interest in composite research.…”
Section: Introductionmentioning
confidence: 96%
“…3 The three fundamental transduction mechanisms used to develop most pressure and strain sensors are piezoelectricity, capacitance, and piezoresistivity. 4 Piezoresistive sensors, which convert pressure or strain stimuli into electrical signals, have gained popularity due to their simple structure, high sensitivity, quick response, low cost, and easy signal collection. 5 Conventionally, flexible substrates like indium tin oxide, polydimethylsiloxane, and cellulose paper have been widely used for sensing applications due to their high scalability and compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Large-volume concrete structures are prone to cracking as a result of temperature and loading. Over time, the structure will accrue damage, resulting in resistance deterioration and, in severe situations, collapse [ 1 , 2 ]. As a result, it is critical to monitor the structure’s health.…”
Section: Introductionmentioning
confidence: 99%